Pengaruh Pemberian Ekstrak Kulit Mangga Arum Manis (Mangifera Indica) Terhadap Kadar Gula Darah Tikus Wistar Jantan Obesitas yang Diinduksi HFD (High Fat Diet) dan Aloksan - Rahmadani, Oktari; Theresia, Yohani; Anggraini, Tri Lidya (Syntax Corporation, 2025)
Obesity is a major risk factor for type 2 diabetes mellitus characterized by insulin resistance and hyperglycemia. Sweet arum mango (Mangifera indica) peel contains bioactive compounds with potential as natural antidiabetic and antioxidant agents. This study aimed to determine the effect of sweet arum mango peel extract on blood glucose levels, body weight, and uric acid levels in obese male Wistar rats induced by HFD (high fat diet) and alloxan. An experimental study with a pretest-posttest control group design used 24 male Wistar rats divided into 4 groups: positive control (Pioglitazone 3 mg) and three treatment groups with mango peel extract at doses of 30, 60, and 120 mg/kgBW. Obesity was induced by high-fat diet administration for 21 days and alloxan 150 mg/kgBW intraperitoneally, followed by extract administration for 14 days. Data were analyzed using ANOVA and post hoc Tukey HSD tests. Phytochemical screening revealed that the extract contained alkaloids, terpenoids, saponins, and steroids. Descriptively, blood glucose levels decreased from 442.05 ± 80.80 mg/dL to 109.50 ± 21.15 mg/dL, but this was not statistically significant between groups (p=0.673). Body weight changes also showed no significant differences (p=0.947). Uric acid levels showed significant differences between treatment groups (p=0.006), with the 120 mg/kgBW dose significantly different from the 30 mg/kgBW (p=0.008) and 60 mg/kgBB doses (p=0.042). Sweet arum mango peel extract demonstrates biological potential in affecting glucose and uric acid metabolism in obese rats, although effects on blood glucose levels and body weight were not statistically significant. Further research with longer duration and optimal dosage is needed to validate the extract's effectiveness.